Associations between prenatal maternal mental health indices and mother–infant relationship quality 6 to 18 months' postpartum: A systematic review. Issue 1 (16th September 2019) - Hazell Raine, Karen; Nath, Selina; Howard, Louise M.; Cockshaw, Wendell; Boyce, Philip; Sawyer, Emily; Thorpe, Karen
ABSTRACT: Maternal mental disorders can significantly impact on children's psychosocial and psychological development, incurring substantial ongoing economic and personal costs. A key mediating mechanism is mother–infant relationship quality (MIRQ). Research studies and perinatal mental health screening initiatives have predominantly focused on depressive symptoms and perinatal depression as predictors of MIRQ. While maternal depression is associated with suboptimal MIRQ, the findings have not been consistent. Personality characteristics are associated with parenting and proneness to depression, presenting a potential addition to prenatal mental health assessment. We conducted a systematic review of studies that have examined the link between prenatal depressive symptoms and/or personality characteristics with postnatal MIRQ. Our findings suggest that both maternal personality traits and depressive symptoms measured in early pregnancy are associated with postnatal MIRQ. A measure of personality characteristics may enhance prenatal mental health assessment, affording opportunities for targeted intervention commencing in pregnancy to improve MIRQ, parenting, maternal mental health outcomes, and infant psychosocial and psychological development, and thereby contributing to the reduction of human and economic cost burdens. RESUMEN: Los trastornos mentales maternos pueden impactar significativamente el desarrollo sicosocial y sicológico de los niños lo cual conlleva considerables continuos costos económicos y personales. Un mecanismo mediador clave es la calidad de la relación madre‐infante (MIRQ). Los estudios investigativos y las iniciativas de exámenes de salud mental perinatales predominantemente se enfocan en los síntomas depresivos y la depresión perinatal como factores de predicción de MIRQ. Mientras que la depresión materna se asocia con una MIRQ inferior al nivel óptimo, los resultados no son consistentes. Las características de la personalidad se asocian con la crianza y la tendencia a la depresión, lo cual presenta un posible punto adicional a la evaluación de salud mental prenatal. Llevamos a cabo una revisión sistemática de estudios que examinaron la conexión entre síntomas depresivos prenatales y/o características de la personalidad con MIRQ postnatal. Nuestros resultados sugieren que tanto las características maternas de la personalidad como los síntomas depresivos medidos durante el temprano embarazo se asocian con MIRQ postnatal. Una medición de las características de la personalidad pudiera mejorar la evaluación de salud mental prenatal lo cual permitiría oportunidades para la intervención enfocada a partir del embarazo con miras a mejorar MIRQ, la crianza, los resultados de salud mental maternos, así como el desarrollo sicosocial y sicológico del infante, contribuyendo así a reducir la carga humana y económica. RÉSUMÉ: Les troubles mentaux maternels peuvent avoir un impact important sur le développement psychosocial et psychologique des enfants menant à des coûts personnels et économiques continus et importants. Un mécanisme de médiation clé est la qualité de la relation mère‐nourrisson (ici abrégé en français QRMN). Les études de recherché et les initiatives de dépistage en santé mentale périnatale ont surtout porté sur les symptômes dépressifs et la dépression périnatale en tant que prédicteurs de la QRMN. Mais alors que la dépression maternelle est liée à une QRMN sous‐optimale, les résultats ne sont pas uniformes et constants. Les caractéristiques de personnalité sont liées au parentage et à la propension à la dépression, présentant un ajout potentiel à l'évaluation de santé mentale prénatale. Nous avons passé en revue systématiquement toutes les études ayant examiné le lien entre les symptômes dépressifs périnataux et / ou les caractéristiques de personnalité avec une QRMN postnatale. Nos recherches suggèrent que les traits de personnalité maternelle et les symptômes dépressifs mesurés durant le début de la grossesse sont à la fois liés à la QRMN postnatale. Une mesure de caractéristiques de personnalité pourrait améliorer l'évaluation de la santé mentale prénatale et offrir des possibilités d'intervention ciblée commençant durant la grossesse, afin d'améliorer la QRMN, le parentage et les résultats de santé mentale maternelle, ainsi que le développement psychosocial et psychologique du nourrisson, contribuant donc à la réduction de la charge du coût humain et économique. ZUSAMMENFASSUNG: Psychische Störungen bei Müttern können die psychosoziale und psychologische Entwicklung von Kindern erheblich beeinträchtigen und laufend ernsthafte wirtschaftliche und persönliche Kosten verursachen. Eine zentrale Mediatorvariable ist die Qualität der Mutter‐Kind‐Beziehung (mother‐infant relationship quality; MIRQ). Forschungsstudien und perinatale Vorsorgeinitiativen zu psychischer Gesundheit befassen sich hauptsächlich mit depressiven Symptomen und perinataler Depression als Prädiktoren für MIRQ. Depressive Symptomatik bei der Mutter ist mit einem suboptimalen MIRQ assoziiert, aber die Ergebnisse stimmen nicht überein. Persönlichkeitsmerkmale zeigen Zusammenhänge zu Elternkompetenz und Depressionsneigung auf, was eine mögliche Ergänzung zur Untersuchung der pränatalen psychischen Gesundheit darstellen könnte. Wir führten ein systematisches Review von Studien durch, die den Zusammenhang zwischen pränatalen depressiven Symptomen und / oder Persönlichkeitsmerkmalen mit postnatalem MIRQ untersuchten. Unsere Ergebnisse legen nahe, dass sowohl mütterliche Persönlichkeitsmerkmale als auch depressive Symptome, die in der Frühschwangerschaft gemessen wurden, mit postnatalem MIRQ assoziiert sind. Ein Maß für Persönlichkeitsmerkmale könnte pränatale Untersuchungen zu psychischer Gesundheit verbessern. Außerdem könnte so die Möglichkeit für gezielte Interventionen ab der Schwangerschaft entstehen, um die MIRQ, die Elternkompetenz, die psychische Gesundheit der Mütter und die psychosoziale und psychologische Entwicklung der Säuglinge zu verbessern und damit zur Verringerung der menschlichen und wirtschaftlichen Belastung beizutragen. 抄録: 妊娠中の母親のメンタルヘルス指標と産後６ヶ月から１８ヶ月の母子関係の質の関連:系統的再検討 母親の精神障害は子どもの心理社会的発達に対して多大な影響を及ぼし、継続的な経済的、個人的な費用が相当発生する。鍵となる仲介メカニズムは母子関係性の質 (MIRQ) である。調査研究と周産期メンタルヘルススクリーニングの新しい取り組みでは優位に MIRQ の予測因子として抑うつ症状と周産期うつ病に焦点を当てている。母親のうつ病はそれほど最良ではない MIRQ と関係づけられていて、調査結果は一貫していない。人格特性は子育てとうつ病の傾向に関係していて、妊娠中のメンタルヘルス評価に対する潜在的な追加要因を示している。 我々は妊娠中の抑うつ症状か人格特性、もしくはその両者と出生後の MIRQ との関連を検討した研究を系統的に検討した。我々の最終提言は妊娠早期における母親の人格傾向と抑うつ症状の両者は出産後の MIRQ に関係しているということである。人格特性の測定は出産前のメンタルヘルスの評価の可能性を高め、妊娠から始まるターゲットとなる介入の機会を与えて、 MIRQ 、子育て、母親メンタルヘルスの結果と乳幼児の心理社会的精神発達を改善させ、それによって人的と経済的コスト負担の削減に貢献するかもしれない。 摘要: 產前6至18個月母親心理健康指數與產後母嬰關係質量的關聯:系統評價 摘要 母親精神障礙嚴重影響兒童的心理社會和心理發展, 造成持續的經濟和個人成本。關鍵的中介機制是母嬰關係質量 (MIRQ)。 研究和圍產期心理健康篩查計劃主要集中在抑鬱症狀和圍產期抑鬱作為 MIRQ 的預測指標。雖然母親抑鬱症與最不理想的 MIRQ 相關, 但研究結果並不一致。人格特徵與養育方式和容易患上抑鬱症有關, 產前心理健康評估或可測量這些東西。我們對研究進行了系統的綜述, 這些研究檢查產前抑鬱症狀和/ 或人格特徵與產後 MIRQ 之間的聯繫。我們的發現表明, 懷孕初期母親的人格特徵和抑鬱症狀均與產後 MIRQ 相關。人格特徵的測量可以加強產前心理健康評估, 為妊娠初期提供干預機會, 改善 MIRQ 丶育兒丶產婦心理健康及嬰兒心理社會和心理發展, 從而有助於減輕人力和經濟成本負擔。 ملخص: الروابط بين مؤشرات الصحة النفسية للأمهات قبل الولادة ونوعية العلاقة بين الأم والرضيع بعد ستة أشهر إلى 18 شهراً من الولادة: استعراض منهجي يمكن أن تؤثر الاضطرابات النفسية للأمهات تأثيرا كبيرا على النمو النفسي –الاجتماعي للأطفال مما له من تبعات اقتصادية وشخصية كبيرة. ومن آليات الوساطة الرئيسية نوعية العلاقة بين الأم والرضيع (MRQ). تركز الدراسات البحثية ومبادرات فحص الصحة النفسية في فترة ما حول الولادة في الغالب على أعراض الاكتئاب والاكتئاب في فترة ما حول الولادة كمؤشرات لـجودة العلاقة بين الأم والرضيع MIRQ. وفي حين يرتبط الاكتئاب الأمومي مع MIRQ دون المستوى الأمثل، فإن النتائج ليست متسقة. وترتبط خصائص الشخصية بالأبوة والأمومة والميل للاكتئاب، مما يشكل إضافة محتملة إلى تقييم الصحة النفسية قبل الولادة. أجرينا مراجعة منهجية للدراسات التي تناولت العلاقة بين أعراض الاكتئاب قبل الولادة و / أو خصائص الشخصية مع MIRQ بعد الولادة. تشير النتائج التي توصلنا إليها إلى أن كل من سمات شخصية الأم وأعراض الاكتئاب التي تقاس في الحمل المبكر ترتبط بـ MIRQ بعد الولادة. قد يعزز قياس خصائص الشخصية تقييم الصحة النفسية قبل الولادة مما يتيح فرص التدخل المستهدف بدءاً من الحمل، لتحسين MIRQ، والرعاية الوالدية، ونتائج الصحة النفسية للأمهات، والنمو النفسي الاجتماعي للرضع، مما يسهم في الحد من التبعات البشرية والاقتصادية.